Thermo-economic assessment of salt hydrate-based thermochemical heat transformer system: heat upgrade for matching domestic hot water production - Li, Wei (2023)
Efficient energy storage technology is a crucial step in achieving the broad deployment of renewable energies. Thermochemical heat transformer (THT), which rely on reversible gas–solid reactions, can provide an option for efficient energy storage and heat upgrade. In this article, a pressurisation-assisted sorption THT system driven by low-grade solar thermal energy is proposed to meet the heat demand of domestic hot water (DHW) production, and different temperature rises can be realised by regulating the water vapour pressure. The thermodynamic and economic performances of the THT systems employing ten kinds of salt hydrates are investigated under various operating conditions. The results indicate that most salts-based THT systems enable output temperatures higher than 60 °C. Two-stage pressurisation systems can further elevate the temperature lift but at the cost of thermodynamic performance. SrBr2·6H2O, K2CO3·1.5H2O, and LiOH·H2O are more promising hydrates for the THT system by taking energy density, temperature lift, and thermo-economic performance into account. Compared to the classical TCES cycle, the temperature lifts attained by the above salts-based single-stage and two-stage pressurisation THT systems are 17.6–19.9 °C and 32.2–37.8 °C, respectively. Multi-objective optimisation results suggest that the optimum exergy efficiency for the SrBr2-, K2CO3-, and LiOH-based systems are 82.47%, 55.08%, and 63.97%, and the corresponding levelized energy costs (LECs) are 0.3549, 0.7132, and 0.5721 $/kWh, respectively. The results of this study demonstrate the significant potential of developing such pressurisation-assisted THT system for heat upgradation targeting DHW production.